Syn-collisional pan-African granite in the northern part Birnin Gwari schist belt in NW Nigeria - Oluyede, Kehinde; KlÃ¶tzli, Urs (International Journal of Advanced Geosciences, 2020)
Syn-collisional granite in the northern part of the Birnin Gwari schist belt consists dominantly of granite and lesser granodiorite and quartzolite. Petrographic and geÂ¬ochemical data revealed three granite groups: the biotite-hornblende granite (quartzolite - BHG); the biotite granite (BG) and the biotite-muscovite granite (BMG). The rocks generally have calc-alkaline and high-K calc-alkaline affinities, and calc-alkalic to alkali-calcic, peraluminous and ferroan and magnesian geochemistry. They are characterized by LILE enrichment, high LREE fractionation factor [(La/Yb) (6.74 to 45.14] with weak to moderate negative Eu (Eu/Eu* = 0.38 to 0.62) and strong negative Nb, P and Ti anomalies. Variation in the behavior of lithophile elements (Ba, Sr and Rb) revealed diverse granite trend such as â€œhigh and low Ba-Srâ€; â€œnormalâ€, â€œanomalousâ€ â€œstrongly differentiatedâ€ and â€œgranodiorite and quartz dioriteâ€ granite. Their display of similar trace elements and REE patterns suggest they are cogenetic. Major and trace element data indicate differentiation of a mafic magma and partial melting of crustal components inherited from shale-greywacke and quartzose sedimentary protoliths in volcanic arc and post collisional settings. The field and geochemical characteristics of this granite suggest that they are similar to other granites in schist belts in other parts of Nigeria, forming the lateral continuation of the same Pan-African magmatic belt.Â Â Â